The relationship between technical performance indicators and running performance in elite Gaelic football. (3rd September 2017) - Mangan, Shane; Ryan, Martin; Devenney, Simon; Shovlin, Aidan; McGahan, Jason; Malone, Shane; O'Neill, Cian; Burns, Con; Collins, Kieran
Abstract: The aim of the current study was to assess whether technical performance relates to positional running demands of elite Gaelic football players. Over a period of three years (2014–2016), four elite Gaelic football teams were monitored using GPS technologies. Four hundred and thirty-two individual player samples were collected from 52 competitive matches. Video analysis software was used to code technical performance indicators in all games. Pearson's correlations were performed between all technical variables and total distance (m) and high-speed distance (≥17 km h −1 ). Total ball in play time had small to medium effects ( r  = .233 to .390, p  ≥ 0.190) on increasing the amount of total distance and high-speed distance run. Similarly, the percentage of short kick-outs taken by the opposition team and total opposition possession time had small to medium effects ( r  = .146–.410, p  ≥ 0.202) in increasing the amount of total distance and high-speed distance run. The number of fouls made in the middle third had the largest negative effect ( r  = −.89 to −.325, p  ≥ 0.439) on running demands. The results of this study give coaches information on how kick-out strategies, passing strategies and defensive strategies impact on running performance.